PHOTOBIOMODULATION OF LEUKOCYTES CULTURED WITH TNF ALPHA AND TITANIUM DISCS - Cavalcanti , Marcos Fernando Xisto Braga; Alves , Rosely Cabette Barbosa; Moraes , Angelina Cirelli; Diomede, Francesca; Trubiani, Oriana; Maria , Durvanei Augusto (Brazilian Journal of Implantology and Health Sciences, 2024)
. Objective: This work evaluated cell proliferation, cell cycle, and lipoperoxidation of populations of neutrophils and lymphocytes, in contact with titanium discs, in an inflamed environment, irradiated with LLL (low-level laser). Background: Dental implants, and titanium screws, used in dental and maxillofacial surgery, can osseointegrate, and support loads, The osseointegrated implant surgery causes trauma and initiates an inflammatory process. Laser photobiomodulation can affect living tissues, accelerating the inflammatory phase and the repair process. Method: lymphocytes and neutrophils were cultured with TNF- (tumor necrosis factor-alpha) to simulate an inflamed environment. They were cultured with titanium discs to simulate osseointegrated implants. To evaluate the laser photobiomodulation effects, neutrophils received 1 irradiation of LLL, and lymphocytes received 3 irradiations of LLL, (every 24 hs) of 50mW, 660 nm AsGaAl (aluminum gallium arsenate) red laser, for 50 sec., 2.5 J and 88.33 J/cm² per session. The cell cycle was analyzed in flow cytometry, and the lipid peroxidation was quantified. Results were statistically evaluated using unpaired one-way ANOVA and Tukey-Kramer analysis (*) p<0.05 at graphpad Prism 8TM. Results: All the treatments increase the levels of ROS inside the neutrophils and lymphocytes. All the groups present changes in the cell cycle increasing DNA synthesis and mitosis, except for the neutrophils that when laser irradiated are not distinct from the control group, and for the lymphocytes that when cultured with TNF- itself increase apoptosis. Conclusion: Laser photobiomodulation after implant placement increases lymphocyte and neutrophil DNA synthesis and mitosis, and this increase was higher in an inflamed environment.